FREQUENCY OF ATRIAL FIBRILLATION IN PATIENTS WITH IMPLANTATION OF VENTRICULAR DEMAND RATE RESPONSIVE AND DUAL CHAMBER RATE-MODULATED PACEMAKER - Khan, Javaidullah; Ahmad Khan, Zahoor; Iqbal, Rashid; Ullah, Sami; Ahmad Khan, Salman; Rizwan (Journal of Postgraduate Medical Institute, 2024)
Objectives: To determine the frequency of AF in patients after implantation of permanent pacemaker. Methodology: This longitudinal observational study was conducted in the department of cardiology Hayatabad Medical Complex from 1st September 2018 to 31st August 2019 through a descriptive cross sectional study design, a total of 58 patients were included in this study. Results: A total of 58 patients were included in the study. Sample size calculated by WHO sample size calculator using 95%confidence interval and 5% error. 29 (50%) patients had no comorbidity, 5 (8.5%) patients were Diabetic, 17 (29.3%) patients were hypertensive, 7 (12.1%) patients were having CAD. 15 (25.9%) Patients had normal Echo Report with ejection fraction >55%, 34 (58.6%) Patients had Preserved LV Function, 9 (15.5%) Patients were recorded with impaired LV Function. 32 (55.2%) had VVIR Device implanted whereas in 26 (44.8%) patients DDDR Device was implanted. 58 (100%) patients had Sinus Rhythm during implantation. At one month follow up, 56 (96.6%) had Sinus Rhythm, 2 (3.4%) patients had Atrial Fibrillation. At one year, 50 (85.2%) patients had sinus Rhythm and 8 (13.8%) patients had AF., and 13 (22.4%) patients had developed Heart Failure. Conclusions: Our study showed AF burden initially decreased significantly but over long-term AF significantly increased progressively